2019
DOI: 10.1371/journal.pone.0213742
|View full text |Cite
|
Sign up to set email alerts
|

Malaria care-seeking behaviour among HIV-infected patients receiving antiretroviral treatment in South-Eastern Nigeria: A cross-sectional study

Abstract: This study assesses malaria prevention and treatment behaviour among people living with HIV/AIDS (PLWHA) in Owerri, South Eastern Nigeria. Although Nigeria bears one of the world’s largest burdens of both malaria and HIV, there is almost no research studying how co-infected patients manage their care. We systematically sampled 398 PLWHA receiving care at Imo State Specialist Hospital and the Federal Medical Centre in Owerri to complete a structured, pre-tested questionnaire on malaria care-seeking behaviour. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…A structured questionnaire, adapted from prior studies on a similar topic (13,14,(20)(21)(22)27,31,32), was administered to participants by trained community health volunteers (CHVs). The questionnaire was initially prepared in English, translated into the local language, Luo, and then back translated to English for consistency.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A structured questionnaire, adapted from prior studies on a similar topic (13,14,(20)(21)(22)27,31,32), was administered to participants by trained community health volunteers (CHVs). The questionnaire was initially prepared in English, translated into the local language, Luo, and then back translated to English for consistency.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…Evidence shows that most of the malaria deaths occur at home without receiving proper medical care, and in case care is sought, it is often delayed (11,12). Several studies have investigated the determinants influencing the timely treatment of malaria among children under five children and have unveiled a spectrum of predictors of timely malaria treatment spanning socio-cultural, physical, and economic dimensions (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Despite all these efforts, the proportion of under-five children in Kisumu East Sub-county receiving timely malaria treatment remains low as evidenced in Kenya Malaria Indicator Survey (KMIS) of 2020 which reported that only 36% of children with recent fever received timely treatment on the same or next day following fever onset (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two cases reported by the Federal Ministry of Health were a 13-year-old sexually active child and a female commercial sex worker from a neighboring West African country (1,10). Nigeria, the most populous nation in Africa, has the third-highest HIV burden and the highest number of orphans due to AIDS in sub-Saharan Africa (11)(12)(13)(14). According to Mitsunaga et al, (15), heterosexual transmission is the main method of transmission for the AIDS epidemic in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The primary causes of morbidity and mortality in underdeveloped countries are HIV and malaria(Yibeltal et al, 2020). Each disease may become more severe and possibly more contagious through co-infection(Chukwuocha et al, 2019;Gumel et al, 2021;Jemikalajah et al, 2021). HIV therapy reduces the effectiveness of antimalarial medications and may exacerbate side effects(Ssentongo et al, 2020).…”
mentioning
confidence: 99%